Efektivitas Formula Krim Tabir Surya Berbahan Aktif Ekstrak Etanol Biji Wali (Brucea javanica L. Merr) - Amini, Almira; Hamdin, Candra Dwipayana; Muliasari, Handa; Subaidah, Windah Anugrah (Pusat Penelitian dan Pengembangan Biomedis dan Teknologi Dasar Kesehatan, 2020)
High intensity of ultraviolet (UV) radiation causes several adverse effect such as erythema, sunburn, pigmentation, early senescence, and skin cancer. These effects can be prevented by using sun protection product. Wali (Brucea javanica L. Merr) is one of natural plants that contain phenol and flavonoid. These compounds are proven to have sunscreen effect. The purposes of this studies are to formulate and evaluate the effectivity of oil-in-water-type sunscreen cream using 1% ethanol extract of Wali seed. The sunscreen cream is developed by using a fusion method and the evaluation of the effectivity is conducted in vivo on the skin of mice (Mus musculus). The formulated sunscreen cream is then tested for its physical properties, including homogenity, pH, spreadability, adhesion, and stability. The effectivity of the formulated cream is also tested by observing the formation of erytema on the skin of mice (Mus musculus). Erythema appearing on the mouse skin is analyzed with ImageJ and SPSS v23 using the one way anova method. The results showed that the ethanol extract of Wali seeds could be formulated into sunscreen cream. Furthermore, the formulated cream was also able to protect the mice skin against the formation of erythema significantly compared to negative controls (p